5/2t - t = 3 + 3/2t please solve
- print Print
- list Cite
Expert Answers
calendarEducator since 2008
write3,662 answers
starTop subjects are Math, Science, and Social Sciences
5/2t - t = 3 + 3/2t
We will combine like terms,
==> 5/2t - 3/2t - t= 3
==> (5-3)/2t - t = 3
==> 2/2t - t = 3
==> 1/t - t= 3
==> Multiply by t.
==> 1 - t^2 = 3t
==> t^2 + 3t -1 = 0
==> t= [ -3 + sqrt(9+4)/ 2 = (-3+sqrt13)/ 2
==> t2= (-3-sqrt13)/2
Then we have two solution.
==> t= { (-3+sqrt13)/2 , (-3-sqrt13)/2 }
Related Questions
- `h(t) = (t + 1)^(2/3) (2t^2 - 1)^3` Find the derivative of the function.
- 1 Educator Answer
- Solve for t in (0,2pi) sin 2t - 3 = 6 sin t - cost
- 1 Educator Answer
- Find f '(t) using the definition of derivative. `f(t) = (2t + 1)/(t+3)` My algebra is not coming...
- 1 Educator Answer
- equationSolve for t in (0,2pi) sin 2t - 3 = 6sin t - cost
- 1 Educator Answer
- `h(t) = t^(3/4) - 2t^(1/4)` Find the critical numbers of the function
- 1 Educator Answer
5/2t - t = 3 + 3/2t
First combine the like terms ( 5/2t and -t )
By combining the like terms, you should get
3/2t = 3 + 3/2t subtract 3/2t on both sides
By subtracting you should get
0 = 3
since 0 does not = to 3 your answer is no solution
5/2t-t= 3+3/2t
One t is basically the same as 2/2t so
5/2t-2/2t= 3+3/2t
Simplify on the left first
3/2t=3+3/2t
Subtract 3/2t from both sides but...
Since 3/2t-3/2t= 0, this means that there is no solution to this problem. Since the variables cancel each other out.
Student Answers